2021
DOI: 10.1111/jphd.12474
|View full text |Cite
|
Sign up to set email alerts
|

Race and payor type for child visits with public health dental hygienist practitioners

Abstract: Purpose: To examine whether growth in visits to public health dental hygiene practitioners (PHDHPs) providing preventative dental services at a pediatric hospital clinic was predominantly among children receiving public insurance and children of minority background from 2013 to 2017. Methods: Longitudinal descriptive data analysis from electronic health records for 6856 children under age 18 years who visited PHDHPs co-located at a hospital clinic in Pittsburgh, PA, from 2013 to 2017. We compared visits betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are relatively few studies of the provision of common dental procedures in pediatric populations by payer type, and they are largely focused on preventive dental procedures ( 10 16 ). A few such studies reported on differences in the average number of therapeutic dental procedures, including endodontic procedures received by children in Wisconsin ( 11 13 ), finding: (1) amongst children enrolled in a private dental insurance plan, children residing in rural and dental health provider shortage areas (DHPSAs) received higher numbers of endodontic procedures than those residing in urban and non-DHPSA areas ( 11 , 13 ), and African American and Hispanic children received significantly more endodontic procedures than white children ( 12 ); (2) Child Medicaid beneficiaries received endodontic procedures at almost twice the rate of children enrolled in a private dental insurance plan and provision of endodontic procedures did not differ by DHPSA ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are relatively few studies of the provision of common dental procedures in pediatric populations by payer type, and they are largely focused on preventive dental procedures ( 10 16 ). A few such studies reported on differences in the average number of therapeutic dental procedures, including endodontic procedures received by children in Wisconsin ( 11 13 ), finding: (1) amongst children enrolled in a private dental insurance plan, children residing in rural and dental health provider shortage areas (DHPSAs) received higher numbers of endodontic procedures than those residing in urban and non-DHPSA areas ( 11 , 13 ), and African American and Hispanic children received significantly more endodontic procedures than white children ( 12 ); (2) Child Medicaid beneficiaries received endodontic procedures at almost twice the rate of children enrolled in a private dental insurance plan and provision of endodontic procedures did not differ by DHPSA ( 13 ).…”
Section: Introductionmentioning
confidence: 99%